Inflammation and ROS in arthritis: management by Ayurvedic medicinal plants. Issue 18 (24th July 2021) - Prasad, Sahdeo; Kulshreshtha, Alok; Lall, Rajiv; Gupta, Subash C.
Abstract : Chronic joint inflammatory disorders like osteoarthritis and rheumatoid arthritis, which are manifested by joint dysfunction, show an upsurge in inflammation and oxidative stress. Abstract : Chronic joint inflammatory disorders like osteoarthritis and rheumatoid arthritis, which are manifested by joint dysfunction, show an upsurge in inflammation and oxidative stress. Although conventional anti-arthritic drugs are being used to relieve pain from arthritic symptoms, they usually cause severe side effects. Traditionally used Ayurvedic medicinal plants are a promising alternative for the management of arthritic symptoms, as they are safe and effective. Ayurvedic medicinal plants improve arthritic symptoms by reducing joint tenderness, joint pain, swelling, bone and cartilage damage, and increasing knee flexion, walking distance and sports activities. These beneficial effects of Ayurvedic medicinal plants on arthritis are mediated through various cellular mechanisms including inhibition of the inflammatory markers NF-κB, cytokines, adipokines, PGE2, NO, iNOS, COX-2, and MMPs and induction of antioxidant status by decreasing free radicals, lipid peroxidation, and myeloperoxidase, and increasing antioxidant enzymes, Nrf2, and HO-1. Thus, a strategy requires using these Ayurvedic medicinal plants to treat arthritis. This article describes the status of inflammation and oxidative stress in arthritic conditions. We also provide evidence that Ayurvedic medicinal plants and their bioactive components are highly effective in improving arthritic symptoms.